Efeitos da dorzolamida à 2% na re-epitelização corneal e nos níveis da metaloprotease-9 na lágrima de gatos com úlcera de córnea induzida experimentalmente - Pizzinatto, Fábio Dumit (2021)
The current study aimed to determine if three-times daily instillation of 2% dorzolamide alters the corneal wound healing time and the early expression of MMP9 in the tears of cats with experimentally induced superficial ulcerative keratitis. Sixteen adult domestic shorthair cats, with an average weight and age of 3.08 kg (range: 2.02 to 5.04 kg) and 3.20 years (range: 1 to 5 years), respectively, were enrolled in this study. The animals were randomly allocated to two diferente groups (eight cats per group). Cats in the treatment group (TG) received 40µL of a 2% dorzolamide (three times daily) while cats in the control group (CG) received 40µL of saline, at the same time point. Both group received one drop of 0.3% tobramycin (four times daily) until the corneas became fluorescein negative. Tears were collected 24 and 48h after keratectomy, and the total MMP-9 was quantified by ELISA. The corneal re-epithelialization rate did not differ between groups (p = 0.26) and ranged from 0.21 to 0.77 mm2 /h. The average time to achieve corneal wound healing did not differ between groups (p = 0.36) and was 65.50±3.62h in the CG and 71.00±4.58h in the TG. The only significant difference with regard the dimensions of the ulcerated areas was observed in the first 24h of evaluation, being the area of the CG 3.34 mm2 larger than the one observed in the TG (p = 0.04). In both groups corneas healed without scarring, pigmentation, or vascularization. At 24h post keratectomy, the level of MMP-9 in the CG was 6.09±2.62 ng/mL higher when compared to level of MMP-9 in the TG at the same time point (p = 0.03). This study showed that the instillation of a BAK-preserved 2% dorzolamide ophthalmic solution did not impair the corneal wound healing time and the early expression of MMP-9 in the tears of cats with experimentally induced superficial ulcerative keratitis. However, our results warrant further investigation of a BAK-preservative free 2% dorzolamide ophthalmic solution in an experiment conducted with a similar methodology.